The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1139/t03-070
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of clogging of landfill leachate collection and drainage systems

Abstract: The findings of a series of studies investigating the clogging of leachate collection and drainage systems for municipal landfill sites are described. Batch tests, column studies, and field-scale "mesocosm" test cells were used to study the development of a thick microbial biofilm covering the surfaces and filling the pore space of the granular drainage media. Within this biofilm, anaerobic microbial consortia effect the stabilization of the organic load (expressed as chemical oxygen demand), with the concurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 11 publications
0
38
0
5
Order By: Relevance
“…Subsequent decrease in effective porosity and interconnectedness of the pore network reduces the hydraulic conductivity of the geosynthetics. The phenomenon results in the decrease of the system drainage capacity [14,21,25,28,37]. The consequent increase of pore water pressure may cause stability problems [11,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent decrease in effective porosity and interconnectedness of the pore network reduces the hydraulic conductivity of the geosynthetics. The phenomenon results in the decrease of the system drainage capacity [14,21,25,28,37]. The consequent increase of pore water pressure may cause stability problems [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical clogging occurs due to the precipitation of iron oxide onto the fibers. These types of clogging are a major concern for drainage in leachate-collection systems [14,16,17,21,35,[37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, uncertainty regarding landfill bottom drainage layers formed from tire shreds remains a relevant issue. Fleming and Rowe [15][16][17] and Paksy et al [18] have researched the reasons for the clogging of the drainage layer with chemically and biologically mediated deposits. However, the process of how the clogging of biological and chemical origin takes place with waste materials in landfills still has not been properly investigated to have the right answer.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of waste affects the composition of leachate. Field and laboratory studies on leachate drainage systems [15] have shown that clogging of drainage and filter materials occurs due to the accumulation of material within the pore space of drainage media, resulting in a decrease in porosity and hydraulic conductivity. Several studies have approved the appropriateness of tires as a landfill drainage material [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Figura VII.7: Esquema del drenaje de un sistema colector de lixiviados: (a) capa continua de drenaje, (b) drenaje francés y tuberías perforadas sobre capa de gravilla (sin escala). Fuente: (Fleming et al 1999) A parte de lo anterior, se debe tener la seguridad de que todo este sistema de recogida y evacuación de lixiviados va a permanecer en el tiempo durante muchos años después de la clausura del vertedero (Fleming et al 2004) ya que los geotextiles, el material granular de drenaje y las perforaciones de las tuberías se pueden obturar por el paso de partículas groseras o lodos y por la acción de la actividad microbiana. Estas obturaciones disminuyen la vida útil de los sistemas de drenaje (Brune et al 1991a).…”
Section: Vii3 Recogida Y Evacuación De Lixiviadosunclassified